Studies on cyclization reactions of 3-amino-2, 4-dihydroxybutanoic acid derivatives. Issue 6 (20th January 2017) - Esgulian, Mathieu; Belot, Vincent; Guillot, Régis; Deloisy, Sandrine; Aitken, David J.
Abstract : Linear derivatives of the title compound are convenient precursors for regioselective cyclizations leading to highly-functionalized γ-lactones, oxazolidinones, oxazolines and aziridines. Abstract : A number of cyclic derivatives of 3-amino-2, 4-dihydroxybutanoic acid are known in the literature but they are often prepared from other cyclic precursors. This study showed that the title compound too may serve as a convenient substrate for cyclization reactions. Using orthogonally-protected linear derivatives, regioselective cyclizations were performed, leading to original and highly-functionalized γ-lactones, oxazolidinones, oxazolines and aziridines. In these reactions a key role was played by the C3 nitrogen group function, while the C2 alcohol function showed no propensity for participation in cyclization reactions.